Ethnic diverse and financing choices affecting of business survival: a case study of New Zealand small- and medium-sized enterprises - Duppati, Geeta (2021)
Purpose. This paper aims to investigate how ethnic diversity and finance options impact the survival of small- and medium-sized enterprises (SMEs) in New Zealand. Design/methodology/approach. This study incorporates survey data and secondary data from the public domain. The surveys were conducted across six sectors of the economy categorised into four main ethnic groups involving six nationalities. This study adopts regression analysis using Probit, Logit and linear probability. Findings. The financing choices of the entrepreneurs were consistent with pecking-order theory. The evidence suggests that information asymmetries are prevalent in New Zealand, as SMEs’ owners perceive significant risk from expanding businesses internationally. There is no relationship between ethnicity bias and the survival of firms. Originality/value. This study provides a contribution to the literature on factors relating to business survival and guides the policymakers to use the benefits of potential factors to increase the survival rate of SMEs.